Active angular control of a sectioned airfoil using shape memory alloys and fuzzy controller - de Abreu, Gustavo Luiz Chagas Manhães [UNESP]; Maesta, Marcelo F. [UNESP]; Lopes Junior, Vicente [UNESP]; De Marqui Junior, Carlos; Faria, Cassio T.; Inman, Daniel J. (Springer Nature, 2015)
The present work illustrates an example of shape memory alloys and fuzzy controllers applied to active angular control of a sectioned airfoil. The main objective of the proposed control system is to modify the camber line of an airfoil based on the relative rotation between the different sections of the profile, given a reference angle. The changes of the sectioned airfoil angle result from the contraction/expansion of the shape memory alloy caused by heating of the wire with an electric current that changes its temperature by the Joule effect. Considering the presence of plant’s nonlinear effects, especially in the mathematical model of the alloy, this work proposes the application of a control system based on fuzzy logic theory. Through numerical and experimental tests, the performance of the fuzzy controller is compared with an on–off controller applied in an airfoil.
Keywords: Active angular control; Fuzzy logic; Sectioned airfoil; Shape memory alloys